Preparation method and application of TiAlWN thin film
Patent Information
- Application Number
- CN202611098532.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-27
AI Technical Summary
(1)本发明提供一种TiAlWN薄膜,所述TiAlWN薄膜的硬度在高的W含量下仍具有较高的硬度,在大范围工艺窗口保持高硬度特征。
Smart Images

Figure CN122979841A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials technology, and in particular to a method for preparing TiAlWN thin films and their applications. Background Technology
[0002] TiAlWN thin film, as a typical multi-component nitride coating material, has gradually become an important choice for tool coating, surface strengthening of precision molds and high-temperature friction components due to its excellent hardness, thermal stability and chemical inertness. Its wear resistance, heat resistance and oxidation resistance provide important guarantees for improving the overall performance of equipment.
[0003] In terms of fabrication processes, physical vapor deposition (PVD) technology has become the main technical approach for preparing TiAlWN thin films due to its advantages in achieving film densification, controllable elemental composition, and high adhesion deposition at relatively low temperatures. Magnetron sputtering technology, through multi-target synergistic deposition, can achieve precise control of the proportions of Ti, Al, W, and nitrogen elements, thereby obtaining films with high hardness and structural stability. Pulsed high-power electromagnetic sputtering (HIPIMS) technology significantly improves the metal ionization rate, enhancing the microstructure density of the film while greatly strengthening the interfacial adhesion between the film and the substrate. These technologies enable the deposited TiAlWN films to not only possess excellent mechanical properties but also maintain long-term stability in high-temperature, high-friction, and corrosive environments. Furthermore, by precisely controlling deposition process parameters, including target power, deposition gas flow rate, substrate temperature, and bias voltage, the grain structure and stress distribution of the film can be further optimized, achieving a synergistic improvement in hardness, toughness, and adhesion. This meets the multiple performance requirements of coating materials under complex working conditions, showing great promise for future applications.
[0004] Due to the limitations of its multilayer structure, the hardness and other properties of TiAlWN thin films change with the W content. That is, the film hardness decreases as the W content increases. The range of W contents that can meet the performance and stability requirements of TiAlWN thin films is relatively small, usually not greater than 20%, which means that the process window is narrow. Summary of the Invention
[0005] This invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, one objective of this invention is to provide a TiAlWN thin film that maintains high hardness even at high W content, retains high hardness characteristics over a wide process window, and exhibits a slight increase in toughness with increasing W content. A second objective of this invention is to provide a method for preparing the TiAlWN thin film described in the first aspect. A third objective of this invention is to provide an application of the TiAlWN thin film described in the first aspect.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention is to provide a TiAlWN thin film, wherein the molar atomic percentage of W in the TiAlWN thin film is 25-50%, the molar atomic percentage of Ti is 10-30%, the molar atomic percentage of Al is 0-30% but not 0%, and the molar atomic percentage of N is 35-60%.
[0007] In some preferred embodiments, the molar atomic percentage of W in the TiAlWN film is 29-47%.
[0008] A second aspect of the present invention is to provide a method for preparing the TiAlWN thin film described in the first aspect, comprising the following steps: The substrate surface is sputtered in a mixed atmosphere of nitrogen and inert gas using a bipolar high-power pulsed magnetron sputtering method. The sputtering targets are tungsten targets and titanium-aluminum targets, which are the anode and cathode of each other.
[0009] High-power pulsed magnetron sputtering (HIPIMS) technology significantly increases plasma density by applying high-power pulses over an extremely short time, thereby greatly enhancing the ionization rate of target atoms. Compared to the less than 1% ionization rate in traditional magnetron sputtering, HIPIMS technology can increase the discharge ionization rate to over 50%. Simultaneously, high-energy ion bombardment effectively improves the interfacial bonding between the thin film and the substrate, enhancing film adhesion and abrasion resistance. Bipolar high-power pulsed magnetron sputtering (BP-HIPIMS) builds upon conventional HIPIMS by using two external targets, each acting as the anode and cathode of the other. When one target is active, the other is at a positive potential, which eliminates accumulated charge on the target surface, improves arcing, and reduces target poisoning.
[0010] Due to the multilayer structure of TiAlWN thin films, properties such as film hardness vary with W content; that is, increasing W content decreases film hardness. The range of W content that can meet the performance and stability requirements of TiAlWN thin films is relatively small, typically not exceeding 20%, resulting in a narrow processing window. High-energy particle bombardment can break the nanolayer interfaces, achieving interface coherence, which can improve film hardness to some extent and broaden the processing window. In TiAlWN thin films, W has a large atomic mass, making it suitable as a bombardment particle. The traditional method is to increase the bias voltage to increase ion energy. However, tungsten targets and titanium-aluminum targets must be deposited under the same bias voltage. Excessively high bias voltages on titanium-aluminum targets may lead to the introduction of a high-stress titanium-aluminum layer. Switching the bias voltage manually or through a program system is cumbersome or increases costs. High-power pulsed magnetron sputtering technology uses short-width, low-frequency pulses with high target peak current density to improve ionization. Bipolar pulsed high-power magnetron sputtering, on the other hand, applies a positive potential to the sputtering target after the negative pulse of high-power pulsed magnetron sputtering, thereby improving deposition efficiency. This invention employs a bipolar high-power pulsed magnetron sputtering method, utilizing the discharge hysteresis of W ions, which allows the ion beam to be maintained for a considerable period of time. By adjusting the discharge time of the target material on the tungsten target, a positive potential is applied to the W ions in the chamber, selectively accelerating the W ions. This achieves multiple acceleration based on bias voltage, plasma pressure, and reverse voltage, enabling W ions to bombard the thin film with extremely high energy, resulting in an extremely dense thin film structure. This overcomes the limitation of narrow process windows in nano-multilayer structures, obtaining thin films with high hardness maintained over a wide range of process windows.
[0011] In some preferred embodiments, the inert gas includes one or more of He, Ne, Ar, or Kr.
[0012] In some preferred embodiments, the working atmosphere pressure of the bipolar high-power pulsed magnetron sputtering method ( p The range is 0.1~5.0 Pa.
[0013] In some preferred embodiments, the volume ratio of nitrogen to inert gas is 1:(5-10), more preferably 1:(6-8).
[0014] In some preferred embodiments, the substrate comprises a pure metal, a metal alloy, or a semiconductor material.
[0015] In some preferred embodiments, the surface working peak current density of the tungsten target ( J t The value is 0.1~1.0 A / cm. 2 Its peak current intensity is the product of peak current density and target surface area.
[0016] In some preferred embodiments, the surface working peak current density of the titanium-aluminum target (J t The value is 0.1~1.0 A / cm. 2 Its peak current intensity is the product of peak current density and target surface area.
[0017] In some preferred embodiments, the power density of the bipolar high-power pulsed magnetron sputtering method is 4~20 W / cm². 2 .
[0018] In some preferred embodiments, the frequency of the bipolar high-power pulsed magnetron sputtering method ( f The frequency range is 100~5000Hz.
[0019] In some preferred embodiments, the discharge time (i.e., pulse width) of the tungsten target within one sputtering pulse cycle is... P w The charging time for the tungsten target is 5~500μs, and the charging time for the tungsten target is 5~300μs.
[0020] In some preferred embodiments, the discharge time (i.e., pulse width) of the titanium-aluminum target within one sputtering pulse cycle is... P w The charging time for the titanium-aluminum target is 5~500μs, and the charging time for the titanium-aluminum target is 200~2000μs.
[0021] In some preferred embodiments, the chamber temperature of the bipolar high-power pulsed magnetron sputtering method is 20~500°C.
[0022] In some preferred embodiments, the substrate rotation speed of the bipolar high-power pulsed magnetron sputtering method is 0~20 rpm.
[0023] In some preferred embodiments, the substrate bias voltage of the bipolar high-power pulsed magnetron sputtering method is 0 to -500V.
[0024] In some preferred embodiments, the working distance of the bipolar high-power pulsed magnetron sputtering method ( d The diameter is 10~200mm.
[0025] The working distance mentioned in this invention refers to the distance from the surface of the aluminum target to the surface of the substrate, i.e., the target-substrate distance.
[0026] In some preferred embodiments, the substrate undergoes a surface pretreatment before sputtering deposition of the TiAlWN film, the surface pretreatment comprising the following steps: Glow etching is used to sputter clean the surface of the substrate. High-energy ion bombardment removes contaminants and oxide layers from the substrate surface, while forming a micro-rough surface, which provides strong adhesion for subsequent sputtered films.
[0027] A third aspect of the present invention is to provide an application of the TiAlWN thin film described in the first aspect in surface strengthening of cutting tools, molds or high-temperature friction components.
[0028] In some preferred embodiments, the temperature-resistant friction component includes engine parts for aerospace vehicles and automobiles.
[0029] The beneficial effects of this invention are: (1) The present invention provides a TiAlWN thin film, wherein the TiAlWN thin film still has high hardness under high W content and maintains high hardness characteristics over a wide range of process windows.
[0030] (2) The present invention also provides a method for preparing the TiAlWN thin film, which is prepared by bipolar high-power pulsed magnetron sputtering. Bipolar high-power pulsed magnetron sputtering applies a positive potential to the sputtering target after the negative pulse of high-power pulsed magnetron sputtering, and accelerates tungsten ions by adjusting the discharge time of the target material to the tungsten target using its reverse voltage, thereby enhancing the bombardment energy of tungsten plasma, and thus obtaining a more dense thin film structure, and obtaining a thin film that can maintain high hardness over a wide range of process windows.
[0031] (3) The TiAlWN film of the present invention has high hardness and density, and is suitable for surface strengthening of cutting tools, molds and engine parts of aerospace and automobiles, etc., to improve their wear resistance, heat resistance and oxidation resistance, and meet the requirements of use under high speed, high load and high temperature conditions. Attached Figure Description
[0032] Figure 1 The cross-sectional SEM image of the TiAlWN thin film prepared for comparison (the white stripe area in the middle is the film surface). Figure 2 The cross-sectional SEM image of the TiAlWN thin film prepared in Example 2; Figure 3 The cross-sectional SEM image of the TiAlWN thin film prepared in Example 3; Figure 4 The cross-sectional SEM image of the TiAlWN thin film prepared in Example 4; Figure 5 The cross-sectional SEM image of the TiAlWN thin film prepared in Example 6; Figure 6The cross-sectional SEM image of the TiAlWN thin film prepared in Example 10; Figure 7 The graph shows a comparison of the hardness and elastic modulus of the TiAlWN films prepared in Examples 2-4, 6, 10 and the comparative example. Detailed Implementation
[0033] The present invention will be further described in detail below through specific embodiments.
[0034] Unless otherwise specified, the raw materials, reagents, or apparatus used in the following examples and comparative examples are all available from conventional commercial sources or can be obtained by existing technical methods. Unless otherwise specified, the test or experimental methods are conventional methods in the art.
[0035] Example 1 This embodiment relates to a TiAlWN thin film, the preparation method of which includes the following steps: (1) Surface pretreatment: In a pure Ar atmosphere, the surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. The deposition chamber pressure is 3.0 Pa, the substrate bias voltage is 800 V, and the etching time is 15 min. The substrate is a cemented carbide.
[0036] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 50 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0037] Example 2 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 100 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0038] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 100 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0039] Example 3 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 150 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0040] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 150 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0041] Example 4 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 200 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0042] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2The tungsten target discharge time was 80 μs, the charging time was 200 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0043] Example 5 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 250 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0044] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 250 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0045] Example 6 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 300 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0046] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 300 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0047] Example 7 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 350 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0048] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 350 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0049] Example 8 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 400 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0050] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 400 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0051] Example 9 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 450 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0052] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 450 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0053] Example 10 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 500 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0054] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 500 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0055] Example 11 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 550 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0056] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 100 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2The tungsten target discharge time was 80 μs, the charging time was 550 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0057] Example 12 This embodiment relates to a TiAlWN thin film, the preparation method of which differs from that of Example 1 only in that the tungsten target charging time is 600 μs, the rest is the same as that of Example 1, including the following steps: (1) Surface pretreatment; same as in Example 1.
[0058] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar (N2 / Ar volume ratio of 2:13), a bipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium-aluminum targets and tungsten targets. The chamber pressure was 0.6 Pa, the chamber temperature was 300 °C, the bias voltage was -100 V, the target-substrate distance was 600 mm, the operating voltage was 900 V, the substrate rotation speed was 5 rpm, and the sputtering power was 5 W / cm. 2 The tungsten target discharge time was 80 μs, the charging time was 100 μs, and the current density was 0.1 A / cm². 2 The titanium-aluminum target discharge time is 50 μs, the charging time is 1500 μs, and the current density is 1.5 A / cm². 2 The deposition time was 120 min, forming a TiAlWN thin film.
[0059] Comparative Example This comparative example relates to a TiAlWN thin film, the preparation method of which includes the following steps: (1) Surface pretreatment: In a pure Ar atmosphere, the surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. The deposition chamber pressure is 3.0 Pa, the substrate bias voltage is 800 V, and the etching time is 15 min. The substrate is a cemented carbide.
[0060] (2) Thin film deposition: In a mixed atmosphere of N2 and Ar, a unipolar high-power pulsed magnetron sputtering power supply was used to sputter titanium aluminum target and tungsten target. The chamber pressure was 0.6 Pa, the chamber temperature was 150 °C, the bias voltage was 100 V, the substrate rotation speed was 5 rpm, the sputtering power was 250 W, the discharge time of tungsten target was 80 μs, the charging time was 50 μs, the discharge time of titanium aluminum target was 50 μs, the charging time was 1500 μs, and the deposition time was 120 min to form TiAlWN thin film.
[0061] The molar atomic percentage of W in the films prepared in Examples 2-4, 6, 10 and the comparative examples is shown in Table 1.
[0062] Table 1. Molar atomic percentage of W in the films prepared in Examples 2-4, 6, 10 and the comparative examples.
[0063] The interfaces of the thin films prepared in Examples 2-4, 6, 10 and the comparative examples were characterized using field emission scanning electron microscopy. The SEM characterization results for the comparative examples and Examples 2-4, 6, and 10 are shown in the appendix. Figure 1-6 According to the characterization results, the cross-section of the TiAlWN thin film prepared in the comparative example ( Figure 1 The TiAlWN films prepared in Examples 2-4, 6, and 10 exhibit a typical columnar crystal structure with insufficient density. In contrast, the TiAlWN films prepared in Examples 2-4, 6, and 10 show a columnar crystal structure, have a dense cross-section, and no obvious defects.
[0064] The hardness and elastic modulus of the TiAlWN films prepared in Examples 2-4, 6, 10 and the comparative example were tested using a nanoindentation tester with a pressure of 10 mN. The test results are shown in the appendix. Figure 7 According to the appendix Figure 7 It can be seen that, compared with the comparative example, even though the W composition in the film has changed significantly, the films prepared in each embodiment still have high hardness, indicating that the TiAlWN film of the present invention can maintain high hardness over a wide range of process windows.
[0065] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A TiAlWN thin film, characterized in that, The TiAlWN thin film has a molar atomic percentage of 25-50% for W, 10-30% for Ti, 0-30% for Al but not 0%, and 35-60% for N.
2. The TiAlWN thin film according to claim 1, characterized in that, The molar atomic percentage of W in the TiAlWN thin film is 29-47%.
3. The method for preparing the TiAlWN thin film according to claim 1 or 2, characterized in that, The substrate was sputtered in a mixed atmosphere of nitrogen and inert gas using a bipolar high-power pulsed magnetron sputtering method, with tungsten and titanium-aluminum targets as sputtering targets.
4. The preparation method according to claim 3, characterized in that, The inert gas includes one or more of He, Ne, Ar or Kr; and / or, the pressure of the mixed atmosphere is 0.1~5.0 Pa, and the volume ratio of nitrogen to the inert gas is 1:(5-10).
5. The preparation method according to claim 3, characterized in that, The substrate may include pure metal, metal alloy or semiconductor material.
6. The preparation method according to claim 3, characterized in that, The surface operating peak current density of the tungsten target is 0.1~1.0 A / cm². 2 ; and / or, the surface operating peak current density of the titanium-aluminum target is 0.1~1.0 A / cm². 2 .
7. The preparation method according to claim 3, characterized in that, The power density of the sputtering is 4~20W / cm². 2 .
8. The preparation method according to claim 3, characterized in that, The discharge time of the tungsten target within one pulse cycle is 5~500μs, and the charging time of the tungsten target is 5~300μs; and / or, the discharge time of the titanium-aluminum target within one pulse cycle is 5~500μs, and the charging time of the titanium-aluminum target is 200~2000μs.
9. The preparation method according to claim 3, characterized in that, The sputtering conditions of the bipolar high-power pulsed magnetron sputtering method include one or more of the following characteristics: The chamber temperature is 20~500℃; The matrix rotation speed is 0~20 rpm; The substrate bias voltage is 0 to -500V; The working distance is 10~200mm.
10. The application of the TiAlWN film according to any one of claims 1-2 or the TiAlWN film prepared by the preparation method according to any one of claims 3-9 in the surface strengthening of cutting tools, molds or high-temperature friction components.